The morning after approaches to the debt crises - Briones, Leonor M. (1988)
The country is presently confronted with an enormous debt problem. The shaping of the present debt crisis can be better understood if we review past events where several factors contributed to the exacerbation of the problem. Several lessons can be learned from this experience, foremost of which are the impositions of disadvantageous terms by creditor banks on debtor countries. A number of solutions have been considered ranging from passive acceptance of the terms to more radical approaches, such as total repudiation of debts. However, a combination of options might be necessary. Some practical considerations are emphasized including the need to strengthen our bargaining position; the debt issue being a public issue must be understood by the people; and the legislature must have a definite role in the formulation of debt policies, among others.
Keywords: External debts